2023
DOI: 10.1038/s41467-023-37551-4
|View full text |Cite
|
Sign up to set email alerts
|

Major proliferation of transposable elements shaped the genome of the soybean rust pathogen Phakopsora pachyrhizi

Abstract: With >7000 species the order of rust fungi has a disproportionately large impact on agriculture, horticulture, forestry and foreign ecosystems. The infectious spores are typically dikaryotic, a feature unique to fungi in which two haploid nuclei reside in the same cell. A key example is Phakopsora pachyrhizi, the causal agent of Asian soybean rust disease, one of the world’s most economically damaging agricultural diseases. Despite P. pachyrhizi’s impact, the exceptional size and complexity of its genome pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 152 publications
0
9
0
Order By: Relevance
“…Phakospora pachyrhizi , Astropuccinia psidii; Figure 2A and B ) and also have very large genomes as a result of rampant TE proliferation. Recent analysis of three isolates of Phakospora pachyrhizi found that, similar to Entomophthorales, Ty3 elements comprise 43% of the genome ( Gupta et al, 2023 ) and the expansion of these elements was predicted to coincide with radiation of host species. We do not yet know if TEs in P. pachyrhizi and the family Entomophthoraceae expanded via similar mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Phakospora pachyrhizi , Astropuccinia psidii; Figure 2A and B ) and also have very large genomes as a result of rampant TE proliferation. Recent analysis of three isolates of Phakospora pachyrhizi found that, similar to Entomophthorales, Ty3 elements comprise 43% of the genome ( Gupta et al, 2023 ) and the expansion of these elements was predicted to coincide with radiation of host species. We do not yet know if TEs in P. pachyrhizi and the family Entomophthoraceae expanded via similar mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The predicted mature protein was subdivided into two domains, with domain A having no distinguishing features, while domain B is histidinerich. BLASTp searches using the mature PpEC48 amino acid sequence against Genbank nr return a sequence annotated as CSEP-04 from P. pachyrhizi (Kunjeti et al 2016) and PpacPPUFV02|3046184 (99.3% identity) from the recently sequenced UFV02 genome (Gupta et al 2023). A comparison of the amino acid sequences of CSEP-04 to PpEC48 identifies a single amino acid polymorphism at position 26, suggesting that these proteins, which were identified in different P. pachyrhizi isolates, are encoded by the same gene.…”
Section: Soybean Rust (Sbr) Is a Foliar Disease Caused By The Obligat...mentioning
confidence: 99%
“…Future investigations could explore the functional implications of these interactions, their expression patterns, and how they collectively impact the virulence strategies of P. pachyrhizi during soybean rust infection. Using the EffectorP program to predict effector candidate proteins in P. pachyrhizi, Gupta et al (2023) identified an average of 850 effector candidates in the genomes of the three isolates that were sequenced. Therefore, our study with 82 effectors covers approximately 1% of the total potential interactions, and it indicates that additional work to establish the P. pachyrhizi metaeffector repertoire will be interesting and necessary to fully understand the functions of effectors in this pathosystem.…”
Section: Soybean Rust (Sbr) Is a Foliar Disease Caused By The Obligat...mentioning
confidence: 99%
“…The impact of soybean rust on yield can be as high as 40–80%, with even a low incidence rate of 0.05% posing a significant risk to farmers and agricultural systems. The disease is ubiquitous in the soybean growing areas of Latin America, where 210 million metric tons of soybean are projected to be produced in 2022/23 ( https://apps.fas.usda.gov/psdonline/app/index.html ) 3 , and on average representing a gross production value of U.S. $115 billion per season ( https://www.ers.usda.gov/data products/season-average-price-forecasts.aspx) 3 . Chemical control is the only method by which to control the disease due to the limited resistant soybean germplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical control is the only method by which to control the disease due to the limited resistant soybean germplasm. In Brazil alone, the cost is estimated to be approximately U.S. $2.8 billion per harvest for managing Phakopsora pachyrhizi ( https://news.agropages.com/News/NewsDetail--−45811.htm ) 3 . The recent number of cases of ASR in the 2022/23 harvest exceeded 119 in nine Brazilian states, and this was an increase of more than 220% in just one season compared to the same period last year between November 2022 and January 2023 ( https://news.agropages.com/News/NewsDetail--−45811.htm ) 2 .…”
Section: Introductionmentioning
confidence: 99%